The relevance of joint contribution of capital to the formation of partnership in Islamic commercial law: an analysis - Sadique, Muhammad Abdurrahman (International Journal of Business, Economics and Law (IJBEL), 2016)
The Islamic legal theory pertaining to partnership venture provides an interesting example of the complex yet logical reasoning behind the formation of rules. An analysis of the rules regarding partnership capital is undertaken in the present study, with a view to understanding their relation to rules on other areas of partnership as well as on commercial transactions in general. The study indicates that each major school of Islamic law had a distinct concept regarding the essential nature of contractual partnership, based on its approach to the relevance of joint capital and liability thereof. This concept is seen to have dictated the rules on all relevant aspects of partnership, in a coherent and logical manner. Understanding such essential concepts is vital for extending the relevance of the rules to situations newly arisen, so that the regularity and consistency of Shari‘ah rules can be maintained.